Defender of Patients’ Rights and Nurses”: Perceptions of Charge Nurses about Competency - Yaghobian , Mahbobeh; Navipour, Hassan; Vanaki , Zohreh (Bangladesh Journal of Medical Science, 2025)
Background Charge nurses are considered as part of the front line managers in healthcare system. The aim of this study was to explore charge nurses’ perceptions of competency. Methods This qualitative study with content analysis approach has been done with 17 semi-structured and deep interviews with 9 Charge Nurses (CNs), 2 matrons, 3 supervisors and 3 head nurses. The deep interview has been collected based on openended questions and if necessary, the exploratory questions and the ones extracted from the nurses’ real experiences in the clinical setting. The content analysis has been done using Zhang (2009) Qualitative Content Analysis Method. Results The data analysis has resulted in extracting 5 themes, 10 categories, 30 subcategories and 166 main codes. Five themes include: selfmanagement, others’ management, clinical competency, professional-legal competency and perceptional-cognitive competency. Conclusion The present study derived results can be used by the on-job training planners so that to promote the CNs’ competency as quickly as possible through executing the short-term training programs and prepare them better for management and clinical responsibilities. BJMS, Vol. 24 No. 03 July’25 Page : 931-937